2018
DOI: 10.2478/romneu-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Chronic Subdural Hematomas Requiring Reoperation: Could Small Trephination Be a Valid Alternative to Conventional Approaches?

Abstract: Background: Chronic subdural hematomas (CSDHs) are one of the most common intracranial lesions treated in a neurosurgical department. They associate significant morbidity and mortality that increase in the case of recurrences requiring reoperation. Despite extensive published literature, there is still significant debate regarding optimal management of CSDHs and their potential recurrence. Objective: Identify factors for recurrence requiring reoperation of CSDHs in order to adjust our management strategies. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Adam et al observed that recurrence requiring reoperation was significantly more in cases where large craniotomy with or without subdural drain placement than small trephine. 14 They also observed that reoperation was found to be significantly more often with laminar type of CT scan and maximal thickness above 22 mm. 14 Even though previous studies suggest craniotomy in presence of membranes, 3,9,11 large craniotomies are associated with higher risk of morbidity, blood loss, and prolonged anesthesia.…”
Section: Discussionmentioning
confidence: 91%
“…Adam et al observed that recurrence requiring reoperation was significantly more in cases where large craniotomy with or without subdural drain placement than small trephine. 14 They also observed that reoperation was found to be significantly more often with laminar type of CT scan and maximal thickness above 22 mm. 14 Even though previous studies suggest craniotomy in presence of membranes, 3,9,11 large craniotomies are associated with higher risk of morbidity, blood loss, and prolonged anesthesia.…”
Section: Discussionmentioning
confidence: 91%